Identifikasi Penyebab Hambatan Supply Chain Management PPDB Menggunakan Causal Loop Diagram - Irfangi, Ahmad; Aziz, Fathul Aminudin; R. Adawiyah, Wiwiek; Darmawati, Dwita (Jurnal Teknologi dan Bisnis, 2020)
The research on supply chain management had been carried out in both manufacturing andservices companies. In practice, supply chain management also could be applied to the education sector.Several researches related to supply chain management had been carried out in universities, especially inthe process admitting new student. The research on new student admintance supply chain management(PPDB) in schools, especially private vocational schools has never been done. In practice, PPDB inprivate vocational school turn out to have challenges, restrictions and obstacles in the process.New ideas and strategies began to emerge about how strategic efforts to increase the number ofnew student. To solve these problems, it is necessary to pay attention and consider the inhibiting factorsand the causes of PPDB. The maaping of inhibiting factors and the causes of PPDB supply chainmanagement was done through a system approach method with a causal loop diagram (CLD) model thatemphasizes the impact of dynamic factors associated with cause and effect problems that effect theadmintance of the quantity of new student. The result obtained were in the form of causal loop diagram(CLD) model as strategic effort in accepting the quantity of new students.